EFEKTIFITAS SENTRA PENEGAKAN HUKUM TERPADU DALAM PENANGANAN TINDAK PIDANA PEMILIHAN UMUM LEGISLATIF TAHUN 2014 DI PROVINSI RIAU - Sihite, Perancis; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Elections are a means of implementation of the people's sovereignty implemented in general, free, confidential, honest, and fair in the Republic of Indonesia based on Pancasila and the Constitution of 1945. In the general election is very common violations include criminal offenses, then for it needed serious treatment by Law Enforcement Center integrated , but in practice problems still occur. The purpose of this thesis , namely : First , how the effectiveness of the Integrated Law Enforcement Center in handling criminal offenses legislative elections in 2014 in Riau Province, Second, barriers Sentra Integrated Law Enforcement in handling criminal offenses legislative elections in 2014 in Riau Province, Third, efforts are being made to overcome the obstacles Sentra Integrated Law Enforcement in handling criminal offenses legislative elections in 2014 in Riau Province. This type of research can be classified into types of sociological research. This type of research is descriptive analysis. Source of data used were obtained through three (3 ) legal materials are the primary legal materials, secondary and tertiary. The data collection techniques were done using two methods ie interviews and review of literature. From the results of research and discussion, there are three main things that can be inferred. First, Handling General Legislative Crime Pemimihan 2014 in Riau province conducted by the Center for Integrated Law Enforcement Riau province is still not effective because of the many cases handled only one case reached the court level, as well as in handling frequent debates which it caused and can lead to the abandonment of the case that is being handled together. Second, barriers in law enforcement by Sentra Gakkumdu election there are two factors: internal factors such as: lack of coordination in Gakkumdu Sentra, Sentra lack of understanding in Gakkumdu, lack of quality and quantity in the Sentra Gakkumdu and external factors such as: people who are less active to report offenses elections are also facilities and infrastructure to support the complete lack of personnel Sentra Gakkumdu. Third, efforts in Overcoming Barriers Sentra Gakkumdu in handling criminal offense namely elections. improving the quality of personnel, utilizing the available infrastructure, and to disseminate Saran, First, the Sentra Gakkumdu Members should equate understanding in handling criminal election. Secondly, Sentra Gakkumdu improve coordination, eliminate sectoral ego, improve the quality and to disseminate to the public. Third, Sentra Gakkumdu need to make new breakthroughs in terms of handling criminal election given time handling a relatively very short. Keyword : Effectiveness - Crime of Election - Legislative